Academic Senate Minutes 2011-09-29 - Academic Senate:::::::::
Special Report: Academic Council on International Programs. Motion to change name of the Gender and Sexual Health Stakeholder's Exploratory Workgroup (motion to amend something previous adopted) approved. Motion to change timeline of the Gender and Sexuality Stakeholder's Exploratory Workgroup (motion to amend something previous adopted).